An experimental evaluation of inhibiting corrosion effect of phosphate glass on mild steel in acidic solution. (15th May 2019) - Ziat, Younes; Abbas, Naseem; Hammi, Maryama; Echihi, Siham
Abstract: The glass inhibitor with 25% P2 O5 –25% CaO–50% K2 O composition was synthesized and its inhibition potential for mild steel in a molar HCl medium has been evaluated experimentally. The inhibition efficiency was predicted through many parameters particularly by weight loss, contact angle measurements, electrochemical, and potentiodynamic polarization analysis. For this purpose, the equivalent circuit model was used for Electrochemical Impedance Spectroscopy (EIS) measurements. The thermodynamic parameters obtained from experimental analysis was used to evaluate the inhibition efficiency variation with temperature. The results were quite interesting and convincible as the increase in inhibition potential was found by increasing phosphate glass concentration and decreasing temperature. In addition, the glass inhibitor was found a mixed inhibitor, affecting both anodic and cathodic corrosion currents and the inhibitor adsorption onto the mild steel surface was followed by Langmuir isotherm. The adsorption phenomenon of glass inhibitor was also confirmed by water contact angle (WCA) measurements.